The Long-Term Cognitive and Schooling Effects of Childhood Vaccinations in China - Hamid R. Oskorouchi; Alfonso Sousa-Poza; David E. Bloom (Institute of Labor Economics (IZA), 2020)
By exploiting rich retrospective data on childhood immunization, socioeconomics, and health status in China (the China Health and Retirement Longitudinal Study), we assess the long-term effects of childhood vaccination on cognitive and educational outcomes in that country. To do so, we apply various techniques (e.g., propensity score and coarsened exact matching and correlated random effects) to different sets of conditioning variables and subsamples to estimate the average treatment on the treated effect of childhood vaccination. Our results confirm that vaccinations before the age of 15 have long-term positive and economically meaningful effects on nonhealth outcomes such as education and cognitive skills. These effects are relatively strong, with vaccinated individuals enjoying about one more year of schooling and performing substantially better later in life on several cognitive tests.
Keywords: I12; I18; I21; 330; cognitive skills; vaccines; China; education